The vagus nerve in appetite regulation, mood and intestinal inflammation - Browning, Kirsteen N. (Gastroenterology, 2016)
Although the gastrointestinal (GI) tract contains intrinsic neural plexuses that allow a significant degree of independent control over GI functions, the central nervous system provides extrinsic neural inputs that modulate, regulate and integrate these functions. In particular, the vagus nerve (VN) provides the parasympathetic innervation to the GI tract, co-ordinates the complex interactions between central and peripheral neural control mechanisms. This review will discuss the physiological roles of the afferent (sensory) and motor (efferent) vagus in regulation of appetite, mood and the immune system, as well as the pathophysiological outcomes of VN dysfunction resulting in obesity, mood disorders and inflammation. The therapeutic potential of VN modulation to attenuate or reverse these pathophysiological outcomes and restore autonomic homeostasis will also be discussed.